Izražanje z acetilholinesterazo povezanega kolagena Q v mišici med regeneracijo po poškodbi - Tominšek, Janko (Medicinski razgledi, 2008)
Collagen Q (Co1Q) is the non-catalytic subunit of acetylcholinesterase asymmetric molecular forms. We examined CoIQ expression in the extrajunctionaland functional regions of innervated and non-innervated regenerating fast sternomastoid (STM) and slow soleus (SOL) muscles. In two groups of rats, the SOL and STM muscles were denervated before injury, whereasin three groups the muscle nerve was left intact. The muscles were injured by cutting all their blood vessels and by injecting a myotoxic anesthetic bupivacaine. The regenerating muscles were isolated for 10 or 60 days after injury. The ColQmRNA levels were determined by quantitative reversetranscription polymerise chain reaction. The extrajunctional Co1Q mRNA levels in the non-innervated regenerating STM and SOL muscles were not significantly different. A short-term innervation increased extrajunctional ColQmRNA levels of both regenerating muscles in comparison to non-innervated regenerates, but the levels were higher in the SOL muscle than in STM muscle (p < 0.01). A long-term innervation of STM muscle regenerates decreased the extrajunctional Co1QmRNA levels (p < 0.01). Co1QmRNA levels in the extrajunctional and former functional regions of non-innervated regenerating STM muscles were not significantly different, however, they became significantly higher in the functional regions than in the extrajunctional regions after 60 days of innervation (p < 0.01). Intrinsic difference between the myogenic precursor cells of fast and slow muscles may be the reason for different response of immature regenerating muscles to innervation. The signaling mechanism, which regulates ColQexpression in the fast muscle functional regions, originates from the motor nerve terminals also during maturation of regenerating muscle fibers.
Keywords: Acetilholinesteraza; Muscle Denervation; Collagen; RNA, prenašalna; Polimerazna, verižna reakcija; Acetylcholinesterase; Kolagen; Rna, Messenger; Polymerase Chain Reaction; Mišica, denervacija; Rats, Wistar; Podgane, Wistar; mišice; poškodbe; oživčenje; regeneracija